2005
DOI: 10.1177/1099800404272223
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Health in Type 2 Diabetes: Nurse-Physician Collaboration in Primary Care

Abstract: The purpose of this study is to examine effects of a nurse-physician collaborative approach to care of patients with type 2 diabetes and to determine possible effect sizes for use in computing sample sizes for a larger study. Forty patients from a family practice clinic with type 2 diabetes were randomly assigned to control or experimental groups. The control group received standard care, whereas the experimental group received standard care plus home visits from a nurse, as well as consultation with an exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 37 publications
2
51
0
Order By: Relevance
“…It is of high importance to strengthen the responsibility and the autonomy of patients with diabetes in order to enhance diabetes self-management and diabetes-related quality of life. In addition, research has shown that nurse-led clinics can be an effective concept of care in primary and in partnership with GPs (General Practitioner) for people suffering from type 2 diabetes (Gabbay et al 2006;Taylor et al 2005;Wong and Chung 2006). Since only seven diabetics were interviewed the validity and reliability of the results are limited.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is of high importance to strengthen the responsibility and the autonomy of patients with diabetes in order to enhance diabetes self-management and diabetes-related quality of life. In addition, research has shown that nurse-led clinics can be an effective concept of care in primary and in partnership with GPs (General Practitioner) for people suffering from type 2 diabetes (Gabbay et al 2006;Taylor et al 2005;Wong and Chung 2006). Since only seven diabetics were interviewed the validity and reliability of the results are limited.…”
Section: Resultsmentioning
confidence: 99%
“…The workload as well as time pressure in primary care has increased considerably within the last years. Studies reveal that diabetes care management is in many cases uncoordinated, integrated health care concepts are absent and patients rarely receive a systematic consultation and education (Gabbay et al 2006;Möller et al 2004;Taylor et al 2005). Social, psychological and biographical aspects of the lives of diabetics are infrequently taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most trials, the length of intervention and the length of follow-up were similar, with only five trials reporting a few months' difference between the end of the intervention and hemoglobin A 1C assessment. 21,23,29,39,49 Most of the studies (29 trials) focused solely on type 2 diabetes, 9 included patients with either type 1 or 2 diabetes, and 3 trials focused on type 1 diabetes. The mean age of the participants was 57.6 years (SD 7.3); 46.0% were men.…”
Section: Study Characteristicsmentioning
confidence: 99%